2009
DOI: 10.1007/s00535-008-2302-6
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided fine-needle aspiration in patients with lymphadenopathy suspected of recurrent malignancy after curative treatment

Abstract: Lymphadenopathy after treatment of malignancy is not a definitive sign of recurrence. Therefore, pathological sampling and diagnosis are essential for determining the appropriate treatment. For this purpose, EUS-FNA is a safe, convenient, and minimally invasive procedure with high diagnostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 22 publications
(28 reference statements)
2
22
0
Order By: Relevance
“…However, EUS-FNA has many advantages over other techniques [39]: (i) the capability to get a sample from a tiny lesion; (ii) the capability to get a sample of the lesion through a part of the intestinal wall and decrease the risk of needle tract seeding; and (iii) the capability to supply extra information about staging of the disease. In particular, EUS-guided FNA can be carried out in the entire pancreas (the hook and tail included) [16, 17], even for difficult or unreachable regions via the percutaneous access or when the percutaneous route is not indicated [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, EUS-FNA has many advantages over other techniques [39]: (i) the capability to get a sample from a tiny lesion; (ii) the capability to get a sample of the lesion through a part of the intestinal wall and decrease the risk of needle tract seeding; and (iii) the capability to supply extra information about staging of the disease. In particular, EUS-guided FNA can be carried out in the entire pancreas (the hook and tail included) [16, 17], even for difficult or unreachable regions via the percutaneous access or when the percutaneous route is not indicated [12].…”
Section: Discussionmentioning
confidence: 99%
“…Needless to say, careful follow-up is necessary after endoscopic resection, but it is difficult for current diagnostic imaging equipment to differentiate whether slightly enlarged lymph nodes, as in the present case, are non-malignant or metastatic [12]. Iwashita et al [13] analyzed the enlarged lymph nodes of 62 patients and reported EUS-FNA sensitivity to be 97% with a specificity of 100%. EUS-FNA was also effective in the present case; therefore, we believe that EUS-FNA can be of assistance in making an accurate diagnosis for patients with enlarged lymph nodes.…”
Section: Discussionmentioning
confidence: 77%
“…Although it might be possible to confirm the pathological diagnosis by EUS-FNA, its sensitivity and specificity in patients with lymphadenopathy suspected of recurrent malignancy is low and has a risk of dissemination in the case of extrinsic tumors. Hence, we performed laparoscopic surgery to resect the tumor as a total excisional biopsy [10]. In the present case, we performed three EMRs, and every pathological examination revealed moderately differentiated adenocarcinoma, which indicates that it is difficult to pathologically predict the primary tumor of metastatic LN.…”
Section: Discussionmentioning
confidence: 86%